1995
DOI: 10.1177/000841749506200505
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting Error Patterns of Children with Mild Motor Difficulties

Abstract: A large proportion of children referred to school-based occupational therapists experience difficulty with handwriting. Illegible handwriting is found to have secondary effects on school achievement and selfesteem. The purpose of this study was to identify handwriting error patterns of children with mild motor difficulties and to examine the relationship between handwriting error patterns and perceptual-motor abilities. Sixty-six children aged 7 to 12 years old with mild motor difficulties were involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Most of the studies on handwriting measured only visual-motor integration with the test VMI of Beery (Daly et al, 2003;Malloy-Miller et al, 1995;Marr et al, 2001;Weil & Amundson Cunningham, 1994). As we have shown, eye-hand coordination associated with visual-motor integration is a predictor of the quality of handwriting.…”
Section: Limitations and Conclusionmentioning
confidence: 55%
See 1 more Smart Citation
“…Most of the studies on handwriting measured only visual-motor integration with the test VMI of Beery (Daly et al, 2003;Malloy-Miller et al, 1995;Marr et al, 2001;Weil & Amundson Cunningham, 1994). As we have shown, eye-hand coordination associated with visual-motor integration is a predictor of the quality of handwriting.…”
Section: Limitations and Conclusionmentioning
confidence: 55%
“…For the dysgraphic group, this relationship was not significant (r = -.02). For the clumsy children, the correlation was significant (r = 40; p < .05) and in the study by Malloy-Miller, Polatajko, Ansett (1995) who administered the VMI and the Handwriting Evaluation Scale (Malloy-Miller, 1985) to children with mild motor difficulties (r = .37; p < .05). Volman, van Schendel, and Jongmans (2006) (Amundson, 1995) and the VMI.…”
mentioning
confidence: 86%
“…One study found a significant association between poor tactile awareness and a handwriting execution/coordination error pattern in children with mild motor impairment. 41 Similarly, children in grade one (ages 6-7y) born preterm demonstrated decreased sensory awareness of individual fingers and lower handwriting legibility scores compared with term peers. 42 A study of low productivity in 26 school-aged children found half showed evidence of finger agnosia, identified in tasks involving imitative finger movement/differentiation.…”
Section: Handwriting Performance Componentsmentioning
confidence: 96%
“…Handwriting problems in children affect them negatively with respect to both their academic performance [13] and their motivation and self-esteem [28]. The development of young children's writing ability is not only considered an essential criterion for success in school [32,35] but also a critical skill that will impact all of us throughout adulthood [15].…”
Section: Introductionmentioning
confidence: 99%